Optimization of Clinical Supervision in Improving Teacher Professionalism at MTsN 1 Lhokseumawe - sulaiman, sulaiman; Nazar, Nazar; Nurhayati, Nurhayati (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to explore and analyze the optimization of clinical supervision in enhancing teacher professionalism at Madrasah Tsanawiyah Negeri 1 Lhokseumawe. In an era of rapidly evolving education, where the demand for quality teaching is increasingly critical, teacher professionalism emerges as a key factor in creating effective and high-quality learning processes. This research employs a qualitative approach using a case study method, allowing for an in-depth exploration of the various dimensions and nuances involved in the practice of clinical supervision.Data were collected through in-depth interviews, direct observations, and analysis of relevant documents, including supervision instruments and evaluation records. The findings reveal that clinical supervision at MTsN 1 Lhokseumawe is implemented in three main stages: preparation, observation, and analysis and evaluation. This process involves close collaboration between the head of the madrasah, the deputy head of curriculum, and the teachers, aimed at providing constructive feedback and supporting the development of pedagogical skills. The research findings indicate that clinical supervision serves not only as a performance evaluation tool but also as a means to enhance teaching quality and student learning outcomes.